Microbial risks in drinking water systems: persistence and public health implications of opportunistic premise plumbing pathogens - Hayward, Claire; Ross, Kirstin E.; Brown, Melissa H.; Bentham, Richard; Nisar, Muhammad Atif; Hinds, Jason; Xi, James; Whiley, Harriet (Frontiers in Microbiology, 2025)
IntroductionThe persistence of opportunistic premise plumbing pathogens (OPPPs) in drinking water plumbing systems poses a significant public health risk that is receiving increasing attention yet remains poorly understood. This study investigated the co-occurrence of OPPPs and the influence of building infrastructure properties on their prevalence.MethodsDrinking water and biofilm samples were collected from hospitals and private residences across Australia to investigate the abiotic and biotic factors contributing to the growth and proliferation of OPPPs.ResultsQuantitative polymerase chain reaction assays revealed that 41% of samples tested positive for Pseudomonas aeruginosa, 26% for Staphylococcus aureus, 26% for Legionella spp., 24% for Legionella pneumophila, and 14% for Acinetobacter baumannii. Furthermore, free-living amoebae, including Vermamoeba vermiformis (46%) and Acanthamoeba spp. (25%), were frequently detected, with Acanthamoeba spp. demonstrating a significant positive correlation with all bacterial OPPPs. Overall, results indicated a statistically higher prevalence of OPPPs in residential properties and in biofilms. However, building characteristics, including stagnation, hot water system type, and building age, had inconsistent influences on individual OPPP prevalence.DiscussionThese results emphasize the need to incorporate risk assessments regarding the complex factors within the premise plumbing environment that contribute to pathogen persistence, to inform evidence based targeted preventative strategies for at-risk populations. These findings are particularly critical for individuals receiving healthcare at home, as inconsistent water treatment and monitoring in residential settings may increase their risk of exposure to OPPPs.